Buckling study on Two-Stage absorption energy coupler. Issue 2 (4th March 2022) - Xu, Ping; Che, Quanwei; Yao, Shuguang; Tan, Bowen
Abstract: A two-stage absorption energy structure composed of an expanding tube and a buffer has been conventionally applied to the couplers of the China Railway High-speed system. Previous investigations have revealed the energy-absorption characteristics of the couplers. However, in dynamic experiments, some of the couplers were found to buckle at the expansion cone. To analyse the buckling problem of the couplers, a simple theoretical model was established and verified via the finite element method (FEM) and experiments. The critical conditions for the couplers buckling and the bending strengths of the expansion tubes were studied. The results indicate that a slight initial misalignment between the expansion cone and outer tube can cause buckling of the couplers. Further, the stabilities of expansion tubes can be significantly improved by increasing the contact area of the expansion cone, reducing the length of expansion tubes, maintaining separation between the expansion cone and the midpoint of the couplers, and increasing the stiffness of expanding tubes. This study is expected to provide guidelines for solving the stability problems of long-stroke expansion tubes and advances the design of such expansion tubes.